English communication needs in Indonesian university - Dwi Poedjiastutie; Fida Akhyar; Masduki Masduki (Universitas Islam Sultan Agung, 2020)
This paper explores the communication needs of students of English Department, Universitas Muhammadiyah Malang (ED UMM) as well as investigates the obstacles in fulfilling their needs. Collecting and analysing data on needs allows teachers to analyse the gap between what has been done and what needs to be done. Accordingly, a Needs Analysis can support the development and implementation of language policies at both macro and micro levels, with far-reaching consequences. The research participants were ED UMM students who are still attending speaking subjects and those who have already completed the speaking subjects. Two stages of data collections: Focus Group Discussion (FGD) and Questionnaire were employed. In FGD, the participants were selected purposively whereas convenience sampling was employed to get the participants for questionnaires. As many as 475 students or equal to 60 % of ED students enrolled at English Department filled in the questionnaires. The findings indicate that to be able to speak in English was students first priority skill to master due to several reasons. To achieve the goals, improving teaching capacity and evaluating institutional policies are required.